The GNAS Complex Locus and Human Diseases Associated with Loss-of-Function Mutations or Epimutations within This Imprinted Gene - DEMİRCİOĞLU, SERAP (KARGER, 2013)
GNAS is a complex imprinted locus leading to several different gene products that show exclusive monoallelic expression. GNAS also encodes the a-subunit of the stimulatory G protein (Gs alpha), a ubiquitously expressed signaling protein that is essential for the actions of many hormones and other endogenous molecules. Gsa is expressed biallelically in most tissues but its expression is silenced from the paternal allele in a small number of tissues. The tissue-specific paternal silencing of Gsa results in different parent-of-origin-specific phenotypes in patients who carry inactivating GNAS mutations. In this paper, we review the GNAS complex locus and discuss how disruption of Gsa expression and the expression of other GNAS products shape the phenotypes of human disorders caused by mutations in this gene. (C) 2013 S. Karger AG, Basel
Keywords: GNAS; Pseudohypoparathyroidism; alpha-Subunit of the stimulatory G protein; PSEUDOHYPOPARATHYROIDISM-TYPE-IB; XL-ALPHA-S; ALBRIGHT HEREDITARY OSTEODYSTROPHY; PROGRESSIVE OSSEOUS HETEROPLASIA; G-PROTEIN; GS-ALPHA; AUTOSOMAL-DOMINANT; HORMONE RESISTANCE; CONTROL REGION; PARATHYROID-HORMONE